EXPLORING THE INFLUENCE OF CORPORATE SOCIAL RESPONSIBILITY ON PURCHASE INTENTION VIA CUSTOMER SATISFACTION IN FAST FOOD FOR GENERATION Z IN INDONESIA - Rabbani, Athalla Rafif; Arafah, Willy (Musytari : Jurnal Manajemen, Akuntansi, dan Ekonomi, 2024)
AbstractThis study aims to analyze the impact of perceived Corporate Social Responsibility (CSR) on purchase intention through satisfaction among Generation Z consumers in Indonesia, specifically in the context of fast food. With the increasing social awareness of society, especially among Generation Z, consumers are now considering the ethical values and social impact of the brands they choose. The research method used was a survey with a cross-sectional explanatory approach, involving 200 respondents from Generation Z. The results of the analysis show that there is a positive relationship between ethical values and the social impact of brands. The analysis shows that there is a positive relationship between CSR perception and satisfaction, as well as between satisfaction and purchase intention. This research contributes to companies formulating effective marketing strategies by considering Generation Z's expectations and preferences towards CSR initiatives.Keywords: Corporate Social Responsibility, Purchase Intention, Satisfaction, Generasi Z, Fast food, Indonesia.